Proactive therapeutic drug monitoring of adalimumab for pediatric Crohn's disease patients: A cost‐effectiveness analysis - Yao, Jiaqi; Jiang, Xinchan; You, Joyce H S (Journal of gastroenterology and hepatology, 2021)
Background and Aim Recent clinical findings showed proactive therapeutic drug monitoring (TDM) of adalimumab (ADL) to improve sustained remission rate in pediatric patients with Crohn's disease (CD). The present study aimed to evaluate the potential cost‐effectiveness of proactive versus reactive TDM of ADL in pediatric patients with CD from the perspective of the US health‐care provider. Methods A Markov model was constructed to estimate outcomes of proactive versus reactive TDM of ADL in a hypothetical cohort of pediatric CD patients who were in remission on ADL maintenance treatment. Model inputs were derived from published literature and public data. Model outcomes included CD‐related direct medical cost and quality‐adjusted life‐years (QALYs). Sensitivity analyses were performed to examine the robustness of base‐case results. Results When compared with the reactive TDM group, the proactive TDM group saved 0.1960 QALYs at lower cost by USD2021 over a 3‐year time frame in base‐case analysis. One‐way sensitivity analysis showed the ADL drug cost to be the most influential factor. Probabilistic sensitivity analysis of 10 000 Monte‐Carlo simulations found the proactive TDM group to gain 0.1958 QALYs (95% confidence interval [CI] 0.1950–0.1966; P < 0.001) and save USD2037 (95%CI USD1943–2131; P < 0.001). Conclusions Proactive TDM for ADL seems to gain higher QALYs at lower cost in pediatric CD patients.